Complete mitochondrial genome of a novel black soldier fly isolate from Jordans - Abeer Albalawneh; Banan Al-Shagour; Sami Alarsan; Monther Sadder; Belal alshorman; Majdi Aledwan; Mousa Abu deah; Saja Abu Znaimah; Yazan AlBalawnah; Ehab Neimat; Mai Deab; Heba Hasan; et al. (Scientific Reports)
Abstract The high-throughput Illumina sequencing technology was employed to decode the complete mitochondrial genome of isolate Jordan_1 black soldier fly (Hermetia illucens). The genome spans 15,699 base pairs (bp) with a GC content of 28.2%, and it includes 13 protein-coding genes, 22 tRNA genes, and two rRNA genes. One InDel and 57 SNPs were revealed when compared to reference black soldier fly mitogenome. Phylogenetic tree was constructed using additional nine isolates from black soldier fly and Drosophila melanogaster as an out-group. The phylogenetic tree reveal that isolate Jordan_1 have common ancestor with an isolate from Kenya under the haplotype C. This study reveals the first report of black soldier fly mitogenome anywhere from the Middle East and North Africa region.